MANAGEMENT PROFILE OF GUIDANCE AND COUNSELING IMPLEMENTATION IN VOCATIONAL SECONDARY SCHOOL - Any Susilowati (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
This article is intended to describe the management of the implementation of counseling and guidance in vocational secondary schools. All data are revealed by using the techniques of observation and interview against informants that have data sources that are widely associated with the management of the implementation of counseling and guidance  In vocational secondary schools, namely the school counselor and some teachers that helps the implementation of counseling and guidance at SMK Negeri I Ponorogo. The results of the descriptive analysis against the management of the implementation of counseling and guidance at SMK Negeri I Ponorogo can be classified in three parts; First, program planning counseling and guidance. Counseling and guidance programs that have been developed at SMK Negeri I Ponorogo has standard and done professionally, because it has been through the planning mechanism, feasibility study, consulting programs and socialization of execution the program. Second, the implementation of a program management counseling and guidance. Implementation of management counseling and guidance at SMK Negeri I Badegan has been done correctly, because it already includes the target learners and stakeholders with system administration and reporting are complete, ranging from program daily, weekly, on a monthly, semiannual and annual, though the supporting facilities and infrastructure facilities is still very minimal. Third, organizational and human resources personnel of counseling and guidance. The conditions of organization and personnel still to be developed, since technically the amount one person concurrently coordinator of counseling and guidance staff assisted with one person taken from teachers of subjects, so haven't been able to provide services maximum, because the comparative number were one teacher with 1200 students.